2023
DOI: 10.25367/cdatp.2023.4.p141-150
|View full text |Cite
|
Sign up to set email alerts
|

Combining protective clothes with human body models for finite element ballistic impact simulations

Abstract: The ballistic deformation of an ultra-high-molecular-weight (UHMW) polyethylene (PE) composite has been subjected numerically to a multi-layered soft ballistic fabric package modelled upon the body contours of the Global Human Body Models Consortium (GHBMC) human body models M50-P and F05-P. The results of the clothing-body-interaction have been investigated and compared to the behavior of anthropomorphic surrogate models made from ballistic clay. For building the fabric model in donned shape, a single ply of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Several studies have investigated the impact resistance and ballistic performance of different composite materials. The results have shown that the difference in velocity and angle significantly affects the energy absorption capacity of the composites [48,49]. Additionally, the orientation of the fibers in the impact direction has been found to improve the impact energy absorption and overall mechanical response of the composites [50,51].…”
Section: Energy Absorptionmentioning
confidence: 93%
“…Several studies have investigated the impact resistance and ballistic performance of different composite materials. The results have shown that the difference in velocity and angle significantly affects the energy absorption capacity of the composites [48,49]. Additionally, the orientation of the fibers in the impact direction has been found to improve the impact energy absorption and overall mechanical response of the composites [50,51].…”
Section: Energy Absorptionmentioning
confidence: 93%